Pro bono [large type] - Perry, Thomas (Thorndike Press large print mystery series., 2025)
"Charles Warren, Los Angeles attorney, has dedicated his career to aiding people in financial straits. In his newest case, helping a young widow find the money missing from her late husband's investment accounts. Charlie recognizes a familiar scheme--one that echoes the con job that targeted his widowed mother years before. Within hours of starting his investigation, Charlie is followed, shot at, and has briefcase stolen. It's clear that someone doesn't want him following the trail of the missing money, but he quickly becomes too entangled in the web of fraud, betrayal, and criminals surrounding the theft to escape its deadly snare"--